The relationship between Co2 emissions, energy consumption, economic growth and FDI: the case of Turkey. Issue 5 (3rd July 2016) - Gökmenoğlu, Korhan; Taspinar, Nigar
ABSTRACT: This study investigates the relevance of the environmental Kuznets curve (EKC) hypothesis in Turkey for the period 1974–2010 using carbon dioxide (CO2 ) emissions, energy consumption, economic growth, and foreign direct investment (FDI) variables. The long-run equilibrium relationship among CO2 emissions, energy consumption, economic growth, and FDI is revealed using the bounds test. The error correction model under autoregressive-distributed lag mechanism suggests that CO2 emissions converge to their long-run equilibrium level by a 49.2% speed of adjustment every year by the contribution of energy consumption, economic growth, and FDI. The Toda–Yamamoto (1995 ) causality test results imply that carbon emissions and FDI, energy consumption, and CO2 emissions have bidirectional causal relationships. On the other hand, there are unidirectional causal relationships running from economic growth and energy consumption to FDI and from economic growth to energy consumption. Our findings provide evidence of the validity of the pollution haven hypothesis, in addition to the scale effect, and the EKC in the case of Turkey.